Compilation of Modern Technologies To Map Genome‐Wide Cytosine Modifications in DNA. (22nd May 2019) - Zeng, Hu; He, Bo; Yi, Chengqi
Abstract: Over the past few decades, various DNA modification detection methods have been developed; many of the high‐resolution methods are based on bisulfite treatment, which leads to DNA degradation, to a degree. Thus, novel bisulfite‐free approaches have been developed in recent years and shown to be useful for epigenome analysis in otherwise difficult‐to‐handle, but important, DNA samples, such as hmC‐seal and hmC‐CATCH. Herein, an overview of advances in the development of epigenome sequencing methods for these important DNA modifications is provided. Abstract : Charting new territory : A wide variety of DNA modification sequencing methods have been developed, including bisulfite‐dependent analysis, protein‐based discrimination methods, bisulfite‐free chemical labeling methods, and direct sequencing of unamplified DNA. This review highlights the development of these DNA modification sequencing methods.